1987
DOI: 10.1002/actp.1987.010380503
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the chain‐end mobility on the melt crystallization of the ethylene oxide (B) sequences in systems containing diblock AB and triblock ABA copolymers with methyl methacrylate (A)

Abstract: Acta Polymerica 38 (1987) Nr. 5 260 DONTH, KRETZSCHMAR e t al. : Influence of the chain-end mobility on the melt crystallization GOWSKI, T. M., KRYSZEWSKI, M., and PVCHERZ, J . : Acta Cryst. C 42 (1986) 172. ,Carl Schorlemmer" Leuna-Merseburg, Sektion Physik, DDR-4200 MerseburgHindering and final blocking of the normal melt crystallization in central ethylene oxide (EO) blocks by methyl methacrylate (MMA) end blocks of increasing lengths in ABA type triblock copolymers synthesized anionicallg in a new way are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

1988
1988
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 17 publications
2
8
0
Order By: Relevance
“…The end block length strongly affects the crystallization behavior of the PEO chains in the block copolymer. As reported by Donth et al [40] no crystallization of PEO chains was observed in triblock copolymers with long poly(methyl methacrylate) (PMMA) end blocks. They investigated end block influence upon the crystallization of central PEO block.…”
Section: Resultssupporting
confidence: 53%
“…The end block length strongly affects the crystallization behavior of the PEO chains in the block copolymer. As reported by Donth et al [40] no crystallization of PEO chains was observed in triblock copolymers with long poly(methyl methacrylate) (PMMA) end blocks. They investigated end block influence upon the crystallization of central PEO block.…”
Section: Resultssupporting
confidence: 53%
“…This clearly shows a strong influence of the POSS segments on the crystallizability of the PEG chains in the block copolymers. These observations agree with those reported in literature for PEO‐based block copolymers . As an example, Siegwart et al found that in PMMA‐ b ‐PEO‐ b ‐PMMA triblock copolymers, the crystallinity of PEO increases with PEO content.…”
Section: Resultssupporting
confidence: 92%
“…These observations agree with those reported in literature for PEO-based block copolymers. [61] As an example, Siegwart et al [62] found that in PMMA-b-PEO-b-PMMA triblock copolymers, the crystallinity of PEO increases with PEO content. Also, a decrease in crystallinity of the PEO has been observed in triblock copolymers, where the central PEO is attached to poly(perfluorohexylethyl methacrylate).…”
Section: Resultsmentioning
confidence: 99%
“…The sharp onset was explained as follows [2, 31. The lower the temperature, the smaller is the size of the critical PEO nucleus (in the order of a few nanometers). Assuming a phase separation at low temperature [2,41 and assuming that the phase decomposition starts also in the few-nanometer-range, then the lower the temperature, the larger and the better purified (after a given annealing time interval) are the regions that are rich with the PEO phase. A size coincidence of the two contrary tendencies is assumed to be the reason for the rather sharp onset temperature TN for nucleation, provided that the crystal nucleation rate is high enough a t such low temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…A size coincidence of the two contrary tendencies is assumed to be the reason for the rather sharp onset temperature TN for nucleation, provided that the crystal nucleation rate is high enough a t such low temperatures. I n the present paper experimental values of the (relative) number density of crystal nuclei are reported for a triblock copolymer A 4 [2] and a blend A3B in the annealing temperature (T5) interval 235 to 260 K for annealing times (t5) between 1 min and 1 11.…”
Section: Introductionmentioning
confidence: 99%